Comparison of constitutive models for meniscus and their effect on the knee joint biomechanics during gait - Simkheada, T.; Orozco, G. A.; Korhonen, R. K.; Tanska, P.; Mononen, M. E. (Computer Methods in Biomechanics and Biomedical Engineering, 2023)
Mechanical behavior of meniscus can be modeled using constitutive material models of varying complexity, such as isotropic elastic or fibril reinforced poroelastic (FRPE). However, the FRPE material is complex to implement, computationally demanding in 3D geometries, and simulation is time-consuming. Hence, we aimed to quantify the most suitable and efficient constitutive model of meniscus for simulation of cartilage responses in the knee joint during walking. We showed that simpler constitutive material models can reproduce similar cartilage responses to a knee model with the FRPE meniscus, but only knee models that consider orthotropic elastic meniscus can also reproduce meniscus responses adequately.